Perancangan Antena Fleksibel dengan Substrat Polydimethylsiloxane Untuk Pendeteksi Tumor Otak - Maulana Hafez Reza; Yusnita Rahayu; Yuyu Wahyu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Cancer is one of the leading causes of death worldwide. Early detection is the best solution for cancer treatment. One of the most promising technologies in the field of medical diagnosis is Ultra-wideband (UWB) microwave imaging technology, because it does not have ionizing properties (Non-Ionizing) and low cost. This paper will propose the design of flexible antenna for brain tumor detections. The proposed antenna is designed using polydimethylsiloxane (PDMS) as a substrate. The simulation results show flexible antenna is work at 5.8 GHz frequency with -29.54 dB value of return loss, 1.06 value of VSWR, 3.1 GHz bandwidth at frequency range of 4.78-7.88 GHz. The radiation pattern is bidirectional and its gain is 2.34 dB. Keywords: Brain tumor detections, Flexible antenna, polydimethylsiloxane, ultra-wideband.